Some features of the floristic and phytocoenotic diversity of Ulmus pumila L. communities in Western Transbaikalia - S. A. Kholboeva (Проблемы ботаники Южной Сибири и Монголии, 2019)
The paper discusses some features of the floristic and phytocoenotic diversity of Ulmus pumila L.communities in Western Transbaikalia. The indigenous elm communities on slope and communities on postagrogenicfallow lands occupy the largest area. A comparative analysis of systematic, ecological, biomorphological structure betweenthe coenofloras of fallow and indigenous elm communities was carried out. The spectrum of predominant families andgenera in the coenofloras shows their high similarity. The range of environmental and biomorphological composition ofstudied elm coenofloras confirms its steppe character and a high level of adaptation of U. pumila to the arid conditions ofthe steppe region. Analysis of phytocoenotic diversity suggests that the recovery succession with the participation of U.pumila in the fallow areas, located mainly on the leveled and flat surfaces of the basins bottoms, leads to the formation ofelm communities with the predominate of friable turf grass in herb layer.